2020
DOI: 10.1111/obr.12962
|View full text |Cite
|
Sign up to set email alerts
|

Changes in physical activity, diet, and body weight across the education and employment transitions of early adulthood: A systematic review and meta‐analysis

Abstract: Summary Early adulthood is a time when individuals go through important life transitions, such as moving from high school into higher education or employment, but the impact of these life transitions on changes in body weight, diet, and physical activity is not known. We searched six electronic databases to July 2019 for longitudinal observational studies providing data on adiposity, diet, and/or physical activity across education or employment transitions in young people aged between 15 and 35 years. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
74
2
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 47 publications
3
74
2
9
Order By: Relevance
“…Our results are mostly in line with previous reviews indicating that events and transitions during young adulthood are oftentimes accompanied by declines in PA [18][19][20][23][24][25][26] and that retirement may offer a window of opportunity [105] for positive changes in PA despite declines in occupational PA and active commuting [19,27]. Moreover, our results indicate a decreasing trend in PA for the transition from primary to secondary school.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Our results are mostly in line with previous reviews indicating that events and transitions during young adulthood are oftentimes accompanied by declines in PA [18][19][20][23][24][25][26] and that retirement may offer a window of opportunity [105] for positive changes in PA despite declines in occupational PA and active commuting [19,27]. Moreover, our results indicate a decreasing trend in PA for the transition from primary to secondary school.…”
Section: Discussionsupporting
confidence: 91%
“…These previous reviews have suggested that the transition from primary to secondary school is associated with decreasing levels of total PA [22]. Moreover, leaving high school [23] and evolving parenthood [24][25][26] are linked to declines in PA, while retirement is linked to increases especially in leisure-time PA and exercise [27].…”
Section: Introductionmentioning
confidence: 99%
“…There are very limited data on changes in diet and eating behaviours across early adulthood life transitions, as reported in our recent systematic reviews [20,21], and we have found no other studies that systematically looked at changes in fast food intake across life transitions. Our finding of a relative decrease in fast food intake on leaving the parental home may initially seem counterintuitive.…”
Section: Comparison With Previous Researchmentioning
confidence: 71%
“…Data from the National Longitudinal Study of Adolescent Health (Add Health), collected at around the same time as the Project EAT study (1996)(1997)(1998)(1999)(2000)(2001)(2002), and using a very similar measure, reported a fast food consumption frequency of 2. [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] reported consuming fast food on a given day [9], with an overall decrease in fast food consumption with age among U.S adults [9].…”
Section: Comparison With Previous Researchmentioning
confidence: 99%
See 1 more Smart Citation